Analisis Pengelolaan Dana Desa Dalam Pembangunan Desa Sumber Agung - Imam Nuryadi; As’ad Isma; Khusnul Istiqomah (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
learn how to manage funds for the development of Sumber Agung village; to understand the perspective of Islamic economics on the management of village funds in dasa Sumber Agung development. Qualitative descriptive research is the focus of this type of research. Primary and secondary data are the sources of data used. Data collection methods include observation, interviews, and documentation. During the data analysis step, which includes collecting data, reducing data, presenting data, and drawing conclusions. The policy of the head of Sumber Agung Village in regulating or managing the village fund budget for the physical and non-physical development of the village has been well implemented. Planning, implementation, and accountability reports are three stages in the process of managing village funds during the development of Sumber Agung Village. Sumber Agung Village has grown significantly as a result of the management of Bolang village funds. The Sumber Agung village community can benefit directly from the implementation of the management of Sumber Agung village funds for village development and overall community welfare. Based on the principles of justice and human obligations as caliphs on earth, the Islamic economic perspective in the management of Bolang village can be said to be positive.